The use of quizizz as a game-based learning tool in improving the mastery of grammar: low proficient l2 learners’ perceptions - Nor Dawirah Rahman (International Journal Of Modern Education (IJMOE), 2023)
It is indubitable that in this digital age, a plethora of game-based platforms have been used globally to teach students English at all levels. It is also imperative to explore the degree of effectiveness of using gamification in English language acquisition so that its benefits in educational settings can be boosted to the fullest. In congruence with that, this paper gleans into low-proficient L2 learners' perceptions towards the use of Quizizz, a game-based learning tool, towards improving their mastery of English grammar, a pivotal element of acquiring English at the tertiary educational level. This study employed a questionnaire to collect quantitative data from 65 students at Universiti Malaysia Sabah who took the Essential Communication Skills subject. Two parts of the questions posed in the questionnaire are Part A, which is on a 5- point Likert scale and comprises ten questions on students' perceptions of Quizizz features and grammar mastery, and Part B, which consists of one checkbox question with four options on the challenges of using Quizizz. The data yielded positive perceptions that the use of Quizizz is indeed a helpful tool to improve students' grasp of English grammar, and most respondents perceived internet connection issues, distraction from the timing and touch screen’s sensitivity that led to accidental incorrect responses, and jitters when answering questions as the central challenges of using Quizizz. Positive feedback obtained from this study serves as supportive evidence that Quizizz should be constantly and broadly used at the university level for low-proficient students to learn and practise grammar lessons and ultimately level up their comprehension of English grammar. At the same time, educators and educational institutions can take some apt measures to address the challenges so that the benefits of learning English grammar through Quizizz can be optimised